ABBASİLERİN İLK YÜZYILINDA “MEVALİ” - Mehmet Nadir Özdemir (BEU Ilahiyat Fakultesi Dergisi, 2019)
This study focuses on the status of the mevâli in the administrative levels and society during the early period of the Abbasid Caliphate. The Abbasid Caliphate which founded on the geographical and relatively political legacy of the Umayyad Caliphate who left large lands with their conquests, chose to give priority to the nations and tribes that supported the revolution while forming their own management paradigm. The conditions and preferences developed after the Abbasid revolution, which was supported by the Arabs, caused the Arabs to remain secondary. Strengthened Khorasan people and mevâli launched the Suubiyya movement under the influence of their past sufferings. This movement, which had a clear understanding in terms of its political and cultural aspects, has been an influential factor in the disintegration of the Muslim world. Mevâli, who had a place in the palace life near the caliph, was strengthened by the positions they gained. Some of them were people who were described as mevâli during the Umayyad period. The rest were slaves. During the early period of Abbasid they served as governor and translator. It can be also said that the ex-mevâli women who had son became very effective in the palace life in this period. The role of Arabs decreased in the military in the Abbasid period as in all other fields. The main factor in the victory of the Abbasid revolution was the Khorasan army. They played a decisive role in the military life. Over time, the Turks became active in the sovereign army which were consisting of the mevâli. In fact, it would not be wrong to say that Mevali was composed of Turks during this period. When the caliphs began to establish an army to be hosted in garrison cities, a surge of mevâli toward cities began. In the early period of the Abbasid dynasty which is considered the last great state of the formation of Islamic civilization, the importance of the concept of mevali became a precursor to the collapse of the claim of caliphate. The activities of mevali weakened this family-based claim, and the peripheral forces became stronger as the central government lost power.